Dimethylethylamine in mould core manufacturing: exposure, metabolism, and biological monitoring. Issue 3 (March 1991) - Lundh, T; Ståhlbom, B; Akesson, B
Abstract : The exposure and metabolism of dimethylethylamine (DMEA) was studied in 12 mould core makers in four different foundries using the Ashland cold box technique. The mean time weighted average (TWA) full work shift DMEA exposure concentration was 3.7 mg/m3. Inhaled DMEA was excreted into urine as the original amine and as its metabolite dimethylethylamine-N-oxide (DMEAO). This metabolite made up a median of 87 (range 18-93) % of the sum of DMEA and DMEAO concentrations excreted into the urine. Occupational exposure did not significantly increase the urinary excretion of dimethylamine or methylethylamine. The data indicate half lives after the end of exposure for DMEA in urine of 1.5 hours and DMEAO of three hours. The postshift summed concentration of DMEA and DMEAO in plasma and urine is a good indicator of the TWA concentration in air during the workday, and might thus be used for biological monitoring. An air concentration of 10 mg/m3 corresponds to a urinary excretion of the summed amount of DMEA and DMEAO of 135 mmol/mol creatinine.